2012
DOI: 10.1038/jcbfm.2012.157
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Basis of AMP-Dependent Thermoregulation and its Relevance to Central and Peripheral Hyperthermia

Abstract: Therapeutic hypothermia is of relevance to treatment of increased body temperature and brain injury, but drugs inducing selective, rapid, and safe cooling in humans are not available. Here, we show that injections of adenosine 5 0 -monophosphate (AMP), an endogenous nucleotide, promptly triggers hypothermia in mice by directly activating adenosine A1 receptors (A1R) within the preoptic area (POA) of the hypothalamus. Inhibition of constitutive degradation of brain extracellular AMP by targeting ecto 5 0 -nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 31 publications
(56 reference statements)
2
46
0
Order By: Relevance
“…7,8 Recently, we showed that AMP prompts hypothermia by activating adenosine (Ado) A1 receptors (A1Rs) on temperature-insensitive hypothalamic neurons of mice, thereby suppressing the thermoregulatory responses that maintain Tb. 9 We also show that AMP-dependent hypothermia reduces prostaglandin-induced fever in mice, having no effect on peripheral hyperthermia induced by dioxymethamphetamine (ecstasy) overdose. 9 Theoretically, AMPdependent cooling might be harnessed to therapeutic hypothermia of ischemic brain injury.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…7,8 Recently, we showed that AMP prompts hypothermia by activating adenosine (Ado) A1 receptors (A1Rs) on temperature-insensitive hypothalamic neurons of mice, thereby suppressing the thermoregulatory responses that maintain Tb. 9 We also show that AMP-dependent hypothermia reduces prostaglandin-induced fever in mice, having no effect on peripheral hyperthermia induced by dioxymethamphetamine (ecstasy) overdose. 9 Theoretically, AMPdependent cooling might be harnessed to therapeutic hypothermia of ischemic brain injury.…”
Section: Introductionmentioning
confidence: 69%
“…9 We also show that AMP-dependent hypothermia reduces prostaglandin-induced fever in mice, having no effect on peripheral hyperthermia induced by dioxymethamphetamine (ecstasy) overdose. 9 Theoretically, AMPdependent cooling might be harnessed to therapeutic hypothermia of ischemic brain injury. In rats undergoing middle cerebral artery occlusion (MCAo), however, AMP increases infarct size probably because of concomitant hypotension and hyperglycemia.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Following identification of the four receptors, Anderson et al (1994) used the available ligands to suggest that adenosine analogs cause hypothermia via adenosine A 1 receptor (A 1 AR) in the central nervous system. Further evidence for a role for A 1 AR includes prevention of AMP hypothermia by an A 1 AR antagonist (Muzzi et al, 2013), loss of the hypothermic effect of N 6 -cyclohexyladenosine in A 1 AR null (Adora1 2/2 ) mice (Johansson et al, 2001), and induction of a hypothermic state with A 1 AR agonist (N 6 -cyclohexyladenosine) injection into the nucleus of the solitary tract (Tupone et al, 2013). These observations firmly established that A 1 AR activation can cause hypothermia (Fredholm et al, 2011).…”
Section: Introductionmentioning
confidence: 74%